2017
DOI: 10.1590/s1518-8787.2017051005409
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and factors associated with falls in adults aged 55 years or more

Abstract: OBJECTIVE The objective of this study is to analyze the frequency and factors associated with falls in adults aged 55 years or more.METHODS This is a study inserted into another population-based study with representative sample of persons aged 40 years or more of the urban area in a medium-sized municipality of the State of Paraná, Brazil, in 2011. That study obtained demographic and socioeconomic data and characteristics related to life habits, health conditions, and functional capacity (n = 1,180). In 2012, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1
12

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 27 publications
0
8
1
12
Order By: Relevance
“…One can also observe a higher prevalence of falls among elderly peo- ple who have no health insurance plan (Table 1), which reinforces the importance of organising the actions provided by practitioners who work in primary healthcare units and family healthcare services. Prato et al 26 suggested the following actions: to encourage the practice of physical activities for muscle strengthening, to promote continuous education on environmental risks and risk attitudes within the context of aging, and to identify individuals at risk of falls. In this sense, it is estimated that 52% of the urban population of Ribeirao Preto use only the public healthcare system, whereas 80% use it occasionally 27 .…”
Section: Discussionmentioning
confidence: 99%
“…One can also observe a higher prevalence of falls among elderly peo- ple who have no health insurance plan (Table 1), which reinforces the importance of organising the actions provided by practitioners who work in primary healthcare units and family healthcare services. Prato et al 26 suggested the following actions: to encourage the practice of physical activities for muscle strengthening, to promote continuous education on environmental risks and risk attitudes within the context of aging, and to identify individuals at risk of falls. In this sense, it is estimated that 52% of the urban population of Ribeirao Preto use only the public healthcare system, whereas 80% use it occasionally 27 .…”
Section: Discussionmentioning
confidence: 99%
“…O declínio da força muscular também pode ser notado em relação à força de preensão palmar, como verificado neste estudo, pois, de acordo com a literatura, os pontos de corte são de 20 kg para mulheres e 30kg para homens 23 . Uma pesquisa realizada com 404 indivíduos com idade igual ou superior a 55 anos, na qual foram avaliados os fatores associados a quedas, foi observado que as maiores chances se encontravam em indivíduos do sexo feminino, com idade igual ou superior a 65 anos, qualidade de sono ruim, diagnóstico de depressão, com dificuldades de subir e descer escadas, considerados dependentes para atividades básicas e com baixa força de preensão palmar 24 . Todavia, neste estudo, não encontramos relação entre a força de preensão palmar e o risco de quedas nos idosos hospitalizados.…”
Section: Discussionunclassified
“…The dependence levels for daily and instrumental activities were not statistically significant with the risk of falling in this population. In the literature, there is no consensus on the association between functional capacity and risk of falls (10)(11) . The relationship between falls and functional disability may be subject to cause and effect bias, and falls in the elderly people may result in functional disability, as well as functional limitations may hamper activities and increase the risk of falling (11) .…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there is no consensus on the association between functional capacity and risk of falls (10)(11) . The relationship between falls and functional disability may be subject to cause and effect bias, and falls in the elderly people may result in functional disability, as well as functional limitations may hamper activities and increase the risk of falling (11) . The impairment of the functional capacity of individuals over 60 years old directly affects the quality of life, as well as simultaneously reaching the family, the community and the health system in which it is inserted.…”
Section: Discussionmentioning
confidence: 99%